2021
DOI: 10.1590/1678-9199-jvatitd-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and toxicological effects of synthesized palladium(II) complex on snake venom (Bungarus sindanus) acetylcholinesterase

Abstract: Background: The venom of the krait ( Bungarus sindanus ), an Elapidae snake, is highly toxic to humans and contains a great amount of acetylcholinesterase (AChE). The enzyme AChE provokes the hydrolysis of substrate acetylcholine (ACh) in the nervous system and terminates nerve impulse. Different inhibitors inactivate AChE and lead to ACh accumulation and disrupted neurotransmission. Methods: The present study was designed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Santos et al 58 reported in their research study that the Ilex paraguariensis ‐induced AgNPs cause a significant inhibition of AChE ex vivo activity. The results are also supported by Ahmed et al, 19 Sher et al, 59 and Haider et al 60 reports that inhibit AChE to elevate the ACh level in AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Santos et al 58 reported in their research study that the Ilex paraguariensis ‐induced AgNPs cause a significant inhibition of AChE ex vivo activity. The results are also supported by Ahmed et al, 19 Sher et al, 59 and Haider et al 60 reports that inhibit AChE to elevate the ACh level in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the NDs can be cured by addressing one or more of the linked situations. The acetylcholine (ACh) hydrolyzes enzyme acetylcholinesterase (AChE) EC 3.1.1.7 has been reported to play a significant role in AD pathology 19 . According to the literature, researchers are working on the pathogenesis of neurodegenerative conditions, but yet no proper treatment is found 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acetylcholine (ACh) hydrolyzes enzyme acetylcholinesterase (AChE) EC 3.1.1.7 has been reported to play a significant role in AD pathology. [ 22 ] According to the literature, researchers are working on the pathogenesis of neurodegenerative conditions, but no proper treatment is found. [ 23 ] Increasing the ACh level in the brain by using AChE inhibitors is thought to be an important approach for the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, the prevalence of dementia was reported to be 2%-6% among older persons (>65 years of age) [14]. Furthermore, numerous factors, such as aging [15] and various pathological disorders (including protein deposition [16], cholinergic deficits [17], neuroinflammation [18], mitochondrial dysfunction [19], and oxidative stress [20]), have been reported as triggers of NDs. Thus, NDs can be cured by addressing one or more of these causative factors.…”
Section: Introductionmentioning
confidence: 99%